RESPOND—a patient-centred programme to prevent secondary falls in older people presenting to the emergency department with a fall: protocol for a multicentre randomised controlled trial. Issue 1 (23rd June 2014) - Barker, A L; Cameron, P A; Hill, K D; Flicker, L; Haines, T P; Lowthian, J A; Waldron, N; Arendts, G; Redfern, J; Forbes, A; Brand, C A; Etherton-Beer, C D; et al.
Abstract : Introduction: Participation in falls prevention activities by older people following presentation to the emergency department (ED) with a fall is suboptimal. This randomised controlled trial (RCT) will test the RESPOND programme, an intervention designed to improve older persons' participation in falls prevention activities through delivery of patient-centred education and behaviour change strategies. Design and setting: A RCT at two tertiary referral EDs in Melbourne and Perth, Australia. Participants: 528 community-dwelling people aged 60–90 years presenting to the ED with a fall and discharged home will be recruited. People who require an interpreter or hands-on assistance to walk; live in residential aged care or >50 km from the trial hospital; have terminal illness, cognitive impairment, documented aggressive behaviour or a history of psychosis; are receiving palliative care or are unable to use a telephone will be excluded. Methods: Participants will be randomly allocated to the RESPOND intervention or standard care control group. RESPOND incorporates (1) a home-based risk factor assessment; (2) education, coaching, goal setting and follow-up telephone support for management of one or more of four risk factors with evidence of effective interventions and (3) healthcare provider communication and community linkage delivered over 6 months. Primary outcomes are falls and fall injuries per person-year. Discussion: RESPOND builds on prior falls prevention learnings and aims to help individuals make guided decisions about how they will manage their falls risk. Patient-centred models have been successfully trialled in chronic and cardiovascular disease; however, evidence to support this approach in falls prevention is limited. Trial registration number: The protocol for this study is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12614000336684).